Cancer‐associated fibroblasts promote tumor cell growth via miR‐493‐5p in intrahepatic cholangiocarcinoma. Issue 3 (8th December 2022) - Toshida, Katsuya; Itoh, Shinji; Harada, Noboru; Morinaga, Akinari; Yugawa, Kyohei; Tomiyama, Takahiro; Kosai‐Fujimoto, Yukiko; Tomino, Takahiro; Kurihara, Takeshi; Nagao, Yoshihiro; Morita, Kazutoyo; Oda, Yoshinao; et al.
Abstract: The association between tumor microenvironment (TME) and cancer‐associated fibroblasts (CAFs) in intrahepatic cholangiocarcinoma (ICC) progression is poorly understood. This study aimed to reveal whether specific microRNAs (miRNAs) in extracellular vesicles (EVs) derived from CAFs were involved in ICC progression. Conditioned medium (CM) and EVs in the CM of CAFs and normal fibroblasts (NFs) derived from ICC specimens were used to investigate the effects on tumor cell lines. miRNA microarray assay was used to examine the miRNAs of EVs derived from CAFs and NFs in ICC, and the effects of miR‐493‐5p on tumor cell lines were examined. Additionally, databases were used to identify miR‐493‐5p targets, and the relationship between prognosis of ICC patients and cocaine‐ and amphetamine‐regulated transcript propeptide (CARTPT), one of the targets of miR‐493‐5p, expression in ICC tissues was retrospectively analyzed. Compared with NF‐derived CM and EVs, CAF‐derived CM and EVs promoted cell lines in proliferation, scratch, migration, and invasion assays. miRNA microarray analysis revealed that miR‐493‐5p was significantly increased in CAF‐derived EVs compared to NF‐derived EVs. Tumor cell lines transfected with miR‐493‐5p were promoted in proliferation and scratch assays. Immunohistochemical staining was performed on 76 ICC specimens; both overall and recurrence‐free survival rates were significantly worse in the CARTPT‐negative group. Univariate and multivariate analyses showed that low CARTPT expression was an independent poor prognostic factor for overall and recurrence‐free survival. Overall, our data suggest that CAFs in the ICC TME suppress CARTPT in tumor cells and promote tumor cells via miR‐493‐5p in EVs. Abstract : This study examined the role of extracellular vesicles derived from cancer‐associated fibroblasts in intrahepatic cholangiocarcinoma (ICC). We found that cancer‐associated fibroblasts secrete miR‐493‐5p‐rich extracellular vesicles, which promote tumor cells. We also found that the expression of cocaine‐ amphetamine‐regulated transcript propeptide, one of the targets of miR‐493‐5p, was significantly correlated with ICC prognosis.